Immune Checkpoint Gene Expression Profiling Identifies Programmed Cell Death Ligand-1 Centered Immunologic Subtypes of Oral and Squamous Cell Carcinoma With Favorable Survival - Yu, Yang; Tang, Huiwen; Franceschi, Debora; Mujagond, Prabhakar; Acharya, Aneesha; Deng, Yupei; Lethaus, Bernd; Savkovic, Vuk; Zimmerer, Rüdiger; Ziebolz, Dirk; Li, Simin; Schmalz, Gerhard (Frontiers in Medicine, 2022)
Objective: This study aimed to identify the programmed death-ligand 1 (PDL1, also termed CD274)-positively correlated immune checkpoint genes (ICGs) and determine the immune subtypes of CD274-centered ICGs combinations in oral squamous cell carcinoma (OSCC). Materials and Methods: Firstly, 95 ICGs obtained via literature review were identified in the Cancer Genome Atlas (TCGA) database in relation to OSCC and 88 such ICGs expression profiles were extracted. The ICGs positively correlated with CD274 were utilized for subsequent analysis. The relationship between the CD274-positively correlated ICGs and immunotherapy biomarkers (tumor mutation burden (TMB), and adaptive immune resistance pathway genes) were investigated and the relationships of these genes with OSCC clinical features were explored. The prognostic values of CD274-positively correlated ICGs and their associated gene pairs were analyzed by performing survival analysis. Results: Eight ICGs were found to be positively correlated with CD274, including CTLA4, ICOS, TNFRSF4, CD27, BTLA, ADORA2A, CD40LG, and CD28. Among the eight ICGs, seven ICGs (CTLA4, ICOS, TNFRSF4, CD27, BTLA, CD40LG, and CD28) were significantly negatively correlated with TMB. The majority of the adaptive immune resistance pathway genes were positively correlated with the CD274-positively correlated ICGs. Survival analysis utilizing TCGA-OSCC data showed that although CD274 was not significantly associated with the overall survival, the majority of CD274-positively correlated ICGs (BTLA, CD27, CTLA4, CD40LG, CD28, ICOS, TNFRSF4) were significantly correlated with overall survival, whereby their low expression predicted a favorable prognosis. Survival analysis based on the gene pair subtypes showed that the combination subtypes of CD274_low/BTLA_low, CD274_low/CD27_low, CD274_low/CTLA4_low, CD8A_high/BTLA_low, CD8A_high/CD27_low, and CD8A_high/CTLA4_low predicted favorable overall survival. Conclusion: The results identified in the current study provide a theoretical basis for prognostic immune subtyping of OSCC and highlight the importance of developing future immunotherapeutic strategies for treating oral cancer. Keywords: PDL1, immune checkpoint genes, oral and squamous cell carcinoma, immune subtypes, prognosis.